Precautionary protection as a guarantee of effectiveness of subjective rights or as effectiveness of the judicial function - Carrillo Rodríguez, Jorge Luis (2022)
The analysis of this article determines if precautionary protection seeks to guarantee the effectiveness of the sovereignty of the power of the State within the scope of the jurisdictional function, to demonstrate the absolute power that it has and make it prevail in order to grant effective justice; or if we are in the position of a different legal meaning, which states that precautionary protection guarantees the effectiveness of the subjective rights of people in a constitutional rule of law, whose supreme purpose is the defense of persons, who have private rights recognized within a constitutional and legal order. To this end, we intend to demonstrate that, currently. the purpose of judicial precautionary protection is not to guarantee the effectiveness of the public power of the State, but to guarantee and make effective the subjective rights and their effect in the jurisdictional sphere.